Newnes radio and RF engineering pocket book. - Winder, Steve (Newnes Pocket Books., 2002)
New material in the third edition includes mobile base station antennas, operation of cellular networks, SAW filters and ceramic resonators, modulation for stereo FM broadcasts, ADPCM, and vocoders. *The essential data and information for modern radio engineering at your fingertips *Based on the practical knowhow of practicing engineers *Ideal for reference and revision.